Enhancement of wave damping within metamaterials having embedded negative stiffness inclusions - Chronopoulos, Dimitrios; Antoniadis, I.; Collet, M.; Ichchou, M. (Elsevier, 2015)
The wave dissipation properties of layered periodic structures are modelled by FE as well as analytical approaches. A linear oscillator incorporating a negative stiffness element and having exceptional energy dissipation properties is exhibited and incorporated within the modelled structures. The structural dynamic stability of both the oscillator and the modelled waveguides is discussed and ensured. The numerical results provide evidence of a drastic increase of several orders of magnitude for the damping ratio of the flexural waves propagating within the structures.